2009
DOI: 10.1002/adma.200803322
|View full text |Cite
|
Sign up to set email alerts
|

On the Fracture Toughness of Advanced Materials

Abstract: Few engineering materials are limited by their strength; rather they are limited by their resistance to fracture or fracture toughness. It is not by accident that most critical structures, such as bridges, ships, nuclear pressure vessels and so forth, are manufactured from materials that are comparatively low in strength but high in toughness. Indeed, in many classes of materials, strength and toughness are almost mutually exclusive. In the first instance, such resistance to fracture is a function of bonding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
426
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 757 publications
(439 citation statements)
references
References 41 publications
7
426
2
4
Order By: Relevance
“…Traditionally, toughness has been thought of as the ability of a material to dissipate deformation energy without propagation of a crack. However, fracture is actually the result of a mutual competition of intrinsic damage mechanisms ahead of the crack tip that promote cracking and extrinsic shielding mechanisms mainly behind the tip that impede it [42,44]. We thus consider the influence of irradiation in terms of how it may affect these two mechanistic components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, toughness has been thought of as the ability of a material to dissipate deformation energy without propagation of a crack. However, fracture is actually the result of a mutual competition of intrinsic damage mechanisms ahead of the crack tip that promote cracking and extrinsic shielding mechanisms mainly behind the tip that impede it [42,44]. We thus consider the influence of irradiation in terms of how it may affect these two mechanistic components.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent mechanism is that of plastic deformation which provides a means of blunting the crack tip through the formation of "plastic" zones. Extrinsic toughening mechanisms, conversely, operate primarily in the wake of the crack tip to inhibit cracking by "shielding" the crack from the applied driving force [41][42][43][44]. Whereas intrinsic toughening mechanisms are effective in inhibiting both the initiation and growth of cracks, extrinsic mechanisms, e.g., crack bridging, are only effective in inhibiting crack growth [42].…”
Section: Corresponding Exposures For In Situmentioning
confidence: 99%
“…[16][17][18][19][20][21][22]), the development of the multiligament zone implies the existence of a rising crack growth resistance (R-curve) behavior in hardmetals [23][24][25][26][27], the size of which is dependent on the width and strength of the ligaments [7,24,28]; and thus, on the microstructural arrangement of the composites under consideration. R-curve behavior may be described as the ability of a microstructure to develop toughening mechanisms on an advancing crack, which can be done, for example, by screening the crack tip from the far-field driving force [21,29,30]. In the case of ceramics toughened by ductile reinforcements, the magnitude of these stresses increases with crack extension due to the formation of new bridges at the crack wake until a plateau is reached.…”
Section: Introductionmentioning
confidence: 99%
“…Since strengthening of materials reduces toughness [1][2][3], the idea for improving strength-toughness balance is always sought. It is reported that the refinement of crystal grains is an effective method for developing strength and toughness in metallic materials without the addition of alloying elements.…”
Section: Introductionmentioning
confidence: 99%